Sequential processing of adhesive tape evidence: Development of latent fingermarks and subsequent characterization using ATR-FTIR spectroscopy - Nimi, Chongtham; Rani, Nisha; Bagga, Aditi; Singh, Rajinder (Journal of forensic sciences, 2025)
Adhesive tapes are often a subject of forensic examinations as they are frequently encountered in a variety of cases involving drugs of abuse, bombings, homicides, kidnappings, robberies, or sexual assaults. The analytical characterization of such adhesive tape evidence can be useful for assessing potential contact between the suspect, the victim, and/or the crime scene. However, adhesive tapes frequently serve as substrates for fingermarks, and the examination of these impressions takes precedence over the characterization of the tape due to the higher evidentiary value associated with fingermarks. This study evaluated the efficacy of commonly available fingermark development methods for fingermarks on adhesive tapes and investigated their effects on the characterization of the adhesive tapes using ATR-FTIR spectroscopy. Gentian violet and iodine fuming were able to develop fingermarks on various types of tapes with good ridge detail clarity and good contrast. These techniques were also compatible with the characterization of the tapes using ATR-FTIR spectroscopy. Iodine fuming did not introduce any additional peaks in the ATR-FTIR spectra. Gentian violet presented a few minor additional peaks at 1644, 1586, and 963 cm . An additional preliminary study on the effect of selected fingermark techniques on chemometric prediction of adhesive tapes was conducted. The results showed that iodine fuming resulted in more prediction accuracy compared to gentian violet. The findings of this study will contribute to determining the strategic choice for the fingermark development on adhesive tapes as well as its subsequent characterization and also strengthen the interpretation of adhesive tape evidence using chemometrics.